2020
DOI: 10.1002/hyp.13681
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of Universal Soil Loss Equation‐based models at the Sparacia experimental area

Abstract: Improving Universal Soil Loss Equation (USLE)‐based models has large interest because simple and reliable analytical tools are necessary in the perspective of a sustainable land management. At first, in this paper, a general definition of the event rainfall‐ runoff erosivity factor for the USLE‐based models, REFe = (QR)b1(EI30)b2, in which QR is the event runoff coefficient, EI30 is the single‐storm erosion index, and b1 and b2 are coefficients, was introduced. The rainfall‐runoff erosivity factors of the USLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…More specifically, Biddoccu et al (2020), applying the RUSLE model to the soils with permanent cover crops, predicted soil losses that were lower or close to soil formation rate in Europe. Bagarello et al (2017, 2020), using the USLE‐M model, reported an underestimation of soil loss for lower‐intensity events.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, Biddoccu et al (2020), applying the RUSLE model to the soils with permanent cover crops, predicted soil losses that were lower or close to soil formation rate in Europe. Bagarello et al (2017, 2020), using the USLE‐M model, reported an underestimation of soil loss for lower‐intensity events.…”
Section: Resultsmentioning
confidence: 99%
“…The MGSLE is one of the most widely used methods for evaluating soil conservation functions, with the advantages of a simple and clear calculation process, easy access to data and high applicability (Bagarello et al, 2020; Kumar et al, 2020). Therefore, this method was used in this study to find the value of the soil conservation function of cultivated land in terms of the difference between the potential soil loss and the actual soil loss, which is the amount of soil conserved.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate gross erosion in the catchments we used the universal soil loss equation (Equation ( 10 )—[ 46 , 54 ]). A more detailed description of each factor and the values for the study areas can be found in the supplements to this paper.…”
Section: Materials and Methodsmentioning
confidence: 99%